Vilka faktorer avgör då skogsägaren söker samarbetspartner för planering och genomförande av skogsvård? - Gerdin, Oskar (SLU/School for Forest Management, 2013)
Silviculture in young stands in Sweden is below the mark concerning what has to be done in the forest, and it is time to solve the problem. The problem will not be solved only by the private forest owners, professional help is needed.